Role of 'Key Farmer' as 'Opinion Leader’ Through Group Communication in Accepting Farmer’s Innovation in South Sulawesi Cocoa Plantation (Peran ‘Key Farmer’ sebagai ‘Opinion Leader’ Melalui Komunikasi Kelompok dalam Penerimaan Inovasi Petani di Sentra Pertanaman Kakao Sulawesi Selatan) - Tuti Bahfiarti (BBPSDMP KOMINFO MAKASSAR, 2016)
The communications group has a central role in communicating the latest innovations in the field of cocoa. In this study used the term 'farmer' as 'key opinion leader' who served and serve to transfer knowledge through group learning cocoa farmers, especially in South Sulawesi. The purpose of this research is to categorize ' key role farmer' as ' opinion leader ' in accelerating innovation acceptance farmers ranging from planting, maintenance, disease, pests, quality, and innovation is the latest plant cocoa. Type of research uses qualitative descriptive approach which describes the role of the farmer' as ' key 'opinion leader. Results of the study found the group communication 'key farmer’ that serve as ‘ opinion leader' became a source of information from the chairman of the group of farmers who have the level of knowledge, motivation, and understanding a skilled technology and then to transfer knowledge to other members of the farmers group. The key role of the farmer in the group functioning seeking informatio, searching informaton, and utilization information, and dissemination of agricultural innovations in the field of cocoa, especially in South Sulawesi. The key role of the farmer is called